Prevalence of potentially reversible dementias in a dementia outpatient clinic of a tertiary university-affiliated hospital in Brazil - Takada Leonel Tadao; Caramelli Paulo; Radanovic Marcia; Anghinah Renato; Hartmann Ana Paula B. J.; Guariglia Carla Cristina; Bahia Valéria Santoro; Nitrini Ricardo (Arquivos de Neuro-Psiquiatria)
The importance of investigating the etiology for dementia lies in the possibility of treating potentially reversible dementias. The aims of this retrospective study are to determine the prevalence of potentially reversible dementias among 454 outpatients seen at the Cognitive and Behavioral Neurology Unit, Hospital das Clínicas, São Paulo University School of Medicine - Brazil, between the years of 1991 and 2001, and observe their evolution in follow-up. Among the initial 454 patients, 275 fulfilled the DSM-IV criteria for dementia. Alzheimer's disease was the most frequent diagnosis (164 cases; 59.6%). Twenty-two cases (8.0%) of potentially reversible dementia were observed, the most frequent diagnoses being neurosyphilis (nine cases) and hydrocephalus (six cases). Full recovery was observed in two patients and partial recovery in 10 patients. Two cases were not treated and eight cases were lost on follow-up. The prevalence found in the present study falls within the range reported in previous studies (0-30%).